Auxin and cytokinin synergism augmenting biomass and lipid production in microalgae Desmodesmus sp. JS07. (August 2020) - Singh, Jyoti; Jain, Deeksha; Agarwal, Pragati; Singh, R.P.
Graphical abstract: Highlights: Influence of phytohormones on algal biomass and lipid accumulation was investigated. Auxin and cytokinin exihibited a synergystic effect on biomass and lipid yield. Phytohormones influenced the activities of antioxidant enzymes SOD, CAT and APX. Phytohormones modified the FAME contents that were desired for high-grade biofuels. Abstract: Microalgae are considered as a promising resource for biodiesel. Nevertheless, their commercial exploitation necessitates considerable impetus towards the development of approaches for increased biomass and lipid production. The present work elucidates the impact of exogenously supplemented auxins, i.e., indole-3-acetic acid (IAA), indole-3-butyric acid (IBA) and indole-3-propionic acid (IPA) and cytokinins, i.e., benzylaminopurine (BAP) and thidiazuron (TDZ) on biomass, lipid content and fatty acid profile of Desmodesmus sp. JS07. Among auxins, IBA improved the biomass and lipid content up to 1.96 ± 0.11 g/L and 34.88 ± 3.87 %, respectively while BAP among cytokinins increased the biomass and lipid content up to 1.88 ± 0.061 g/L and 31.84 ± 1.33 % respectively. Further, the cumulative impact of IBA (10 mg/L) and BAP (5 mg/L) resulted in their synergistic effect by stimulating biomass and lipid content up to 2.34 ± 0.032 g/L and 42.43 ± 1.88 % respectively. Auxins stimulated the superoxide dismutase activity, and cytokinins increased the enzymes (catalase and ascorbate peroxidase), scavenging reactive oxidative species, thereby regulating ROS homeostasis in microalgae. A significant alteration in the fatty acid profile owing to the type and dosage of phytohormones was detected. Hence, the strategy employing phytohormones could prove to be a meaningful approach for biofuel production.